2006
DOI: 10.1016/j.jcrs.2006.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of residual stromal bed and flap thickness in primary and repeat laser in situ keratomileusis in myopic patients

Abstract: Intraoperative pachymetry of the stromal bed during retreatment is strongly recommended as the residual stromal bed and flap thickness changes between primary and retreatment. There is a tendency for the measured stromal bed at retreatment to be thinner than the calculated stromal bed and for the flap to be thicker than previously measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Conversely, overestimation can lead to inadvertent thinning of the stromal bed beyond 250 μm and, theoretically, may increase the risk for keratectasia. [3][4]51 The current study had several limitations. This type of study is hampered by the different algorithms each device uses for reporting CCT, yet one can only examine the results that each device reports.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely, overestimation can lead to inadvertent thinning of the stromal bed beyond 250 μm and, theoretically, may increase the risk for keratectasia. [3][4]51 The current study had several limitations. This type of study is hampered by the different algorithms each device uses for reporting CCT, yet one can only examine the results that each device reports.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2] This is especially important in patients considered for enhancement surgery since their CCTs are more likely to be too thin for safe treatment. [3][4] Although Ultrasound pachymetry (USP) is the gold standard approach to measure CCT, high inter-observer and inter-instrument variation in measurement has been described. [5][6] The measurement error of USP may arise from a lack of meticulous centration of the measurement, oblique incidence of the probe to the cornea, lack of a fixation light for gaze control, variability of sound speed across tissues, or even the effect of the topical anesthetic agent.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Minimum corneal thickness (MCT) is an important parameter in surgical planning and in the detection of pathology in certain corneal and refractive surgery procedures, in which accurate assessment of MCT and its location is crucial. [12][13][14][15][16] Errors in pachymetric measurement are factors in poor surgical outcomes, including ectasia after laser in situ keratomileusis. [17][18][19] Corneal topographic assessment can be inaccurate in the presence of motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Intraoperative handheld ultrasound (US) is often routinely performed during primary LASIK to measure the thickness of the residual stromal bed immediately after the flap has been created and before the ablation is performed. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] These data can be used to confirm that sufficient tissue is available before proceeding with the ablation. Before retreatment, the predicted ablation depth can be subtracted from the intraoperative RST obtained during the primary procedure after flap creation to estimate the RST after the retreatment.…”
mentioning
confidence: 99%
“…Some surgeons also use a handheld US pachymeter to obtain an RST measurement intraoperatively after lifting the flap during a retreatment and will proceed with the ablation only if sufficient tissue is available. [9][10][11]17,19,20 The repeatability of handheld US has been studied for central corneal thickness (CCT) measurements, [21][22][23][24][25][26][27][28][29] for which the method was designed. However, although handheld US is routinely used intraoperatively to measure RST and flap thickness, its validity in measuring thicknesses as low as those found for RST has not been verified; to date, no study has reported the repeatability of intraoperative handheld US for RST measurements.…”
mentioning
confidence: 99%